Lnk-dependent axis of SCF–cKit signal for osteogenesis in bone fracture healing - Matsumoto, Tomoyuki (The Rockefeller University Press, 2010)
The therapeutic potential of hematopoietic stem cells/endothelial progenitor cells (HSCs/EPCs) for fracture healing has been demonstrated with evidence for enhanced vasculogenesis/angiogenesis and osteogenesis at the site of fracture. The adaptor protein Lnk has recently been identified as an essential inhibitor of stem cell factor (SCF)–cKit signaling during stem cell self-renewal, and Lnk-deficient mice demonstrate enhanced hematopoietic reconstitution. In this study, we investigated whether the loss of Lnk signaling enhances the regenerative response during fracture healing. Radiological and histological examination showed accelerated fracture healing and remodeling in Lnk-deficient mice compared with wild-type mice. Molecular, physiological, and morphological approaches showed that vasculogenesis/angiogenesis and osteogenesis were promoted in Lnk-deficient mice by the mobilization and recruitment of HSCs/EPCs via activation of the SCF–cKit signaling pathway in the perifracture zone, which established a favorable environment for bone healing and remodeling. In addition, osteoblasts (OBs) from Lnk-deficient mice had a greater potential for terminal differentiation in response to SCF–cKit signaling in vitro. These findings suggest that inhibition of Lnk may have therapeutic potential by promoting an environment conducive to vasculogenesis/angiogenesis and osteogenesis and by facilitating OB terminal differentiation, leading to enhanced fracture healing.